Interviews : an introduction to qualitative research interviewing - Kvale, Steinar (Thousand Oaks, Calif. Sage Publications, 1996)
Why hasn't TQM (total quality management) worked as well in the United States as it has elsewhere? In the United States, employees seem to prefer recognition of individual achievement over recognition of the work team. Could the American cultural emphasis on the individual be a crucial factor? This engagingly written book demonstrates that the recent participatory management failures are the result of a lack of appreciation role of rugged individualism. Offering an alternative, person-centered leadership, which puts the individual at the very center of the management approach, Plas demonstrates effective, psychology-based, person-centered management techniques through use of contemporary examples - many of them drawn from her research and consulting work with successful U.S. businesses and CEOs."--Jacket.
Includes bibliographical references and index.
Keywords: Interviewing in sociology; Interviewing; Sociology -- Research -- Methodology; Qualitative research